2012
DOI: 10.5546/aap.2012.214
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de efectividad de la ventilación de alta frecuencia oscilatoria en pacientes pediátricos con insuficiencia respiratoria aguda en un centro de alta complejidad

Abstract: Arch Argent Pediatr 2012;110(3):214-220 / 214 RESUMEN Introducción. La ventilación de alta frecuencia oscilatoria (VAFO) es un recurso terapéuti-co ante la hipoxemia refractaria a la asistencia respiratoria mecánica convencional (ARMc), y en el tratamiento del síndrome de escape aéreo. Un metaanálisis reciente concluyó que la VAFO parece disminuir la mortalidad en niños posneonatales y adultos. En este contexto, es importante la evaluación de los resultados en el uso rutinario de esta tecnología. Objetivos. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The mortality observed in our study is similar to that reported internationally ; however, other studies have reported an improved oxygenation but not mortality improvement. In our study, a significantly better survival was obtained with the combined treatment of the surfactant and recruitment manoeuvres than the survival observed in the control group.…”
Section: Discussionsupporting
confidence: 89%
“…The mortality observed in our study is similar to that reported internationally ; however, other studies have reported an improved oxygenation but not mortality improvement. In our study, a significantly better survival was obtained with the combined treatment of the surfactant and recruitment manoeuvres than the survival observed in the control group.…”
Section: Discussionsupporting
confidence: 89%